Penetration Failure Mechanisms of Armor-Grade Fiber Composites under Impact - Lee, B.L.; Walsh, T.F.; Won, S.T.; Patts, H.M.
The penetration failure mechanisms of "armor-grade" fiber-reinforced composites with very low resin content were assessed under transverse impact loading in comparisonwith those of dry reinforcing fabrics. Failure of dry fabrics consisted of the successive fracture of individual yarns along the periphery of the penetrating head as well as the movement of yarns slipping off from the penetrator. In contrast, the principal yarns in the composites, which faced the penetrating head, failed to carry the load mostly through fracture due to the constraint of the resin matrix and the reduced yarn mobility. As a result, the composites absorbed more energy than the fabrics. The ratio of the number of broken yarns in the fabrics to that of the composites correlated quite well with the corresponding ratio of energy absorbed, confirming that fiber straining is responsible for most of the energy absorption in penetration failure. Numerical modeling was utilized to show that yarn slippage in the fabrics results in a smaller effective penetrator radius leading to a decrease in energy absorption capacity with equal penetrator masses. Although the resin matrix itself did not absorb significant amounts of energy, it certainly had an indirect effect on the energy absorption capacity of composites by influencing the number of yarns broken. Stiffer resin matrix prevented the yarn movement to a greater degree and thereby forced the penetrator to engage and break more yarns. Up to the thickness of 3 mm, the dependence of the kinetic energy for full perforation of composites on the laminate thickness was close to the case of ductile monolithic materials such as polycarbonate or aluminum but in less linear fashion. The deviation from the linearity was attributed to a unique mode of tensile failure of armor-grade composites inwhich a critical level of kinetic energy for full perforation is lowered by the mobility of yarns.
Keywords: PENETRATION FAILURE, BALLISTIC IMPACT; DROP-WEIGHT IMPACT; STATIC PUNCTURE; FIBER-REINFORCED COMPOSITES